Identyfikacja roli i wpływu projektów na funkcjonowanie organizacji - Krzos, Grzegorz (The Identification of the Role and Impact of Projects on Orgąnization Functioning, 2008)
The aim of this article is to present the various ways of managing projects by the EU in private and public sector institutions. The results of studies carried out show that these projects have a strong influence on the situation of a company and that the international standards of project management are not being used in most of private and public sector institutions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 112-119